The Medici return [large type] - Berry, Steve, 1955- (Berry, Steve, 1955- Cotton Malone novels, 2025)
"Cotton Malone is on the hunt for a forgotten 16th century Pledgeof Christ--a sworn promise made by Pope Julius II that evidences a monetary debt owed by the Vatican, still valid after five centuries,now worth in the trillions of dollars. But collecting that debt centers around what happened to the famed Medici of Florence--a family that history says died out, without heirs, centuries ago. Two more things also hang in the balance: who will become the next prime minister of Italy, and who will be the next pope. Finding answers to all three proves difficult until Cotton realizes that everything hinges on when, and if, the Medici return."--